Estimating nitrate leaching and denitrification by simultaneous use of Br and 15N tracers - Bakar, Rosenani Abu; Goulding, Keith W T; Webster, Colin P; Poulton, Paul R; Powlson, David S (Wiley, 1994)
Losses or nitrogen (N) by leaching were estimated in three experiments using bromide (Br) as a tracer. An estimate or denitrification was also made, by difference, by combining the estimate of leaching with a measure of total loss of applied N using 15N. This was compared with a direct measure of denitrification made using acetylene inhibition. Bromide proved to be a poor tracer for nitrate (NO3) leaching at two of the three sites, Brimstone and Hoosfield. Performance was rather better at the Broad Mead site. Problems in using Br were associated with (a) difficulties in measuring small concentrations of Br close to background in soil, and (b) reactions involving N such as immobilisation and mineralisation that rapidly change NO3 pools but do not affect Br. Use of Br in field experiments is unlikely to provide reliable estimates of NO3 leaching over timescales of several weeks as used here unless much more frequent sampling is done. Simultaneous measurements of total losses of N using a 15N tracer were combined with estimates of NO3 leaching using Br to calculate denitrification; these estimates were compared with measurements of denitrification using acetylene inhibition. Agreement was poor because of (i) the lack of reliability of the acetylene inhibition technique, and (ii) the very large errors associated with calculating denitrification as the difference between an estimate of NO3 leaching and total N losses.